THE ROLE OF THE INSTITUTE FOR EMERGENCY MEDICINE BELGRADE IN THE SIMULATION EXERCISE OF THE EMERGENCY SERVICES ON THE OCCASION OF THE WORLD DAY OF REMEMBRANCE FOR ROAD TRAFFIC VICTIMS - Andjelic, Sladjana Lj; Colakovic, Goran (Halo 194 Scientific Journal of Emergency Medicine, 2025)
On the occasion of World Day of Remembrance for Traffic Accident Victims, 11/17/2024. a joint exercise of all emergency services was held. Traffic accident simulation (SN) was organized by the Traffic Safety Agency and the Ministry of Internal Affairs, in cooperation with the Institute for Emergency Medicine (ZZUM) Belgrade and the Serbian Red Cross. In the designed scenario, a traffic accident occurred in which a pedestrian was injured while crossing the tracks outside the marked pedestrian crossing. At the same time, an accident involving three vehicles takes place at another intersection. ZZUM teams acted according to the protocol for taking care of a traffic accident with a large number of injured persons. The doctor of the first arriving triage team, according to the START triage algorithm, categorized the injured according to the urgency of treatment into three triage categories (RED; YELLOW; GREEN) and marked them with triage tapes. Out of a total of six injured: two were from the red, two from the yellow and two from the green category. In addition to the ZZUM teams, the police, the fire and rescue service and the helicopter unit also participated in the further treatment of the injured.